First hero - Blade, Adam (Chronicles of Avantia, 2012)
Fifteen-year-old Tanner, with the good Beast Firepos the Flame Bird, is waiting to avenge his father's death by warlord Derthsin when Avantia is menaced by an evil army seeking the pieces of the Mask of Death, which allows its wearer to control all Beasts, and Tanner, aided by twins Gwen and Geffen, sets out to find the pieces first.